STRENGTHENING JUNIOR HIGH SCHOOL STUDENTS’ LEARNING MOTIVATION THROUGH SELF-CONTROL AND FAMILY SUPPORT - Karina Karina; Nur Ainy Sadijah; Regi Ramadan (CV. TOTUS TUUS, 2026)
Learning motivation is essential for sustaining adolescents' engagement, persistence, and academic development, yet preliminary evidence from a public junior high school indicated that 61% of students had low motivation. This study examined self-control and family support as simultaneous predictors of learning motivation among junior high school students. A quantitative cross-sectional predictive design was used. The population comprised 580 students, from whom 231 participants were selected through grade-based quota sampling with sample size guided by the Krejcie-Morgan procedure. Data were collected using Likert-type scales measuring learning motivation, self-control, and family support and were analyzed through multiple linear regression in SPSS 26. The model was significant, F(2, 228) = 216.574, p < .001, and explained 65.5% of the variance in learning motivation (R = .809, R2 = .655, adjusted R2 = .652). Self-control was a positive predictor (B = .559, beta = .256, t = 5.884, p < .001), while family support showed a stronger positive contribution (B = .468, beta = .663, t = 15.264, p < .001). The findings indicate that motivated learning in early adolescence is jointly associated with students' capacity to regulate impulses and with informational, emotional, instrumental, and appraisal support from their families. Schools should therefore combine self-regulation development with structured family engagement. Longitudinal, multi-school, and multi-informant research is recommended to test causal pathways and contextual variation.